2020
DOI: 10.1093/omcr/omaa101
|View full text |Cite
|
Sign up to set email alerts
|

Malignant hyperthermia, a rare perioperative complication: case series and literature review

Abstract: Malignant hyperthermia is a rare complication of general anesthesia appearing as an acute and potentially lethal hypermetabolic state in people carrying a genetic anomaly expressed in skeletal muscles. Malignant hyperthermia has been scarcely described in sub-Saharan Africa. Herein, we present three cases of malignant hyperthermia occurring in the perioperative period in Cameroon. The authors wish to draw attention to the clinical presentation of this rare but potentially lethal emergency, for timely diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Malignant hyperthermia (MH) is a fatal pharmacogenetic hypermetabolic disorder that occurs when patients with mutation of RYR1 gene located on chromosome 19q13.1 exposed under volatile anesthetics (ie, halothane, isoflurane, sevoflurane, desflurane, enflurane) or in conjunction with a depolarizing muscle relaxant (especially, succinylcholine). 9 Despite its rarity, a statistic about it demonstrates that 40% of this incidence occurs during the anesthesia period of head and neck surgery 10 ; thus, plastic surgery departments should take especial vigilance. In this case, MH occurred during the anesthesia period of cervical plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant hyperthermia (MH) is a fatal pharmacogenetic hypermetabolic disorder that occurs when patients with mutation of RYR1 gene located on chromosome 19q13.1 exposed under volatile anesthetics (ie, halothane, isoflurane, sevoflurane, desflurane, enflurane) or in conjunction with a depolarizing muscle relaxant (especially, succinylcholine). 9 Despite its rarity, a statistic about it demonstrates that 40% of this incidence occurs during the anesthesia period of head and neck surgery 10 ; thus, plastic surgery departments should take especial vigilance. In this case, MH occurred during the anesthesia period of cervical plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant hyperthermia (MH) is an autosomal dominant muscle disorder characterised by hypermetabolism which arises from mutations in RYR1 (Foo et al, 2022 ). The reported incidence is 1 in 5000 to 100,000 individuals and it is triggered by certain anesthetic compounds in affected persons (Denborough, 1998 ; Krivosic‐Horber, 2014 ; Ndikontar et al, 2020 ; Nelson & Litman, 2014 ). Fatality can occur if not properly identified and promptly treated (Foo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors stressed early diagnosis, management (with dantrolene) and follow‐up could help prevent death (Ndikontar et al, 2020 ). Genetic testing provides a non‐invasive and cost‐effective method of assessing risk in affected individuals and families; Bennette et al reported that disclosing IFs from genetic screening in healthy individuals led to reduced cost and increased quality of life years (QALYs) (Bennette et al, 2015 ; Sei et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%